Science Through Activities - Gupta, Arvind (JOURNAL OF INDIAN EDUCATION, 2010)
The search for teaching science meaningfully to rural children has been a very challenging task for educators. Many attempts have been made in the past and there are several lessons to be learnt from them. Some, like the Hoshangabad Science Teaching Programme (HSTP) worked in over a 1000 village schools for over two decades. The HSTP unleashed the creativity of thousands of children and teachers, but was ultimately shut down by the State government. Every innovation leaves behind seeds for future innovation. Is the chalk-talk method best suited to teach science? Is the ability to regurgitate a few definitions an indicator of comprehension? Isn’t expensive glassware and sophisticated plastic equipment in a typical school science laboratory a little out of sync with the lives of ordinary village children? Shouldn’t the learning of science be made more contextual – something which a child can relate to with her everyday experiences? How do children learn science? Perhaps science is learnt best when it goes beyond the four walls of the classroom and addresses the concerns and problems of the larger community. Then science becomes alive and vibrant. Also the use of local materials for making simple science models helps children assimilate them better. Apart from outlining tried and tested field experiments the talk will be interspersed with practical and fascinating demonstrations.